Prevalence of overweight in children with bone fractures: a case control study - Valerio Giuliana; Gallè Francesca; Mancusi Caterina; Di Onofrio Valeria; Guida Pasquale; Tramontano Antonino; Ruotolo Edoardo; Liguori Giorgio (BMC, 2012)
Abstract Background Children's fractures have been enlisted among orthopaedics complaints of childhood obesity. Unhealthy lifestyle behaviours may contribute to increased risk. This study described the prevalence of overweight/obesity in children and adolescents reporting a recent fracture in relation to gender, dynamic of trauma, and site of fracture. Methods Four-hundred-forty-nine children and adolescents with fracture and 130 fracture-free controls were recruited from a large children's hospital. The interaction between overweight and gender, dynamic of trauma, site of fracture was explored. Sports participation, television viewing, and calcium intake were also investigated. Results Overweight/obesity rate was increased in girls with fracture either at the upper or the lower limb (p= 0.004), while it was increased only in boys with fracture at the lower limb (p <0.02). Overweight/obesity rate did not differ between groups with low or moderate trauma. TV viewing ≥ 2 hrs was more frequent in children with fractures than controls (61.5% vs 34.5%, p =0.015) in the overweight/obese group. Conclusions The increased prevalence of overweight/obesity in children with fractures is related to gender and site of fracture. Higher levels of sedentary behaviours characterize overweight children reporting fractures.